Isolation, identification, and control of a resistant bacterium strain found in Ku shui rose pure dew. Issue 2 (8th January 2021) - Ling, Lijun; Yang, Caiyun; Ma, Wenxia; Zhao, Yunhua; Feng, Shenglai; Tu, Yixin; Wang, Nan; Li, Zibin; Lu, Lu
Abstract: Rose pure dew is commonly used in food and cosmetic industries. A bacterial was isolated from rose pure dew, followed, the morphological, physiological, biochemical, and molecular biology were used to the identification. The pathogenicity of the strain and the broad‐spectrum antibacterial activity of pure dew were detected. The strain was subjected to testing at temperature gradients as well as to antibacterial tests against food preservatives and drugs. The isolate was considered as Burkholderia cepacia MG1 carrying toxicity‐related genes. The antibacterial test revealed that only B. cepacia MG1 could grow normally in pure dew, with the optimum inactivation condition of 52°C for 15 min. It is sensitive to ε‐polylysine hydrochloride, sodium diacetate, kanamycin, nalidixic acid, and ofloxacin. The tested antibiotics could inhibit the pathogen, which provides a theoretical basis for the treatment of patients infected. It is necessary to control the quality of rose pure dew productions, which is helpful for our health. Practical applications: Microbial contamination of food or insufficient/inefficient sterilization during food processing or production can bring about significant economic losses to the food industry as well as pose a serious threat to the health of consumers. In this study, B. cepacia MG1 was isolated from Ku shui rose dew, and the pathogenicity of the identified isolate was established. Accordingly, the prevention and treatment of B. cepacia MG1‐contaminated food were conducted by temperature treatment or the use of food preservatives and antibiotics so as to provide a scientific theoretical reference for the prevention and treatment of B. cepacia MG1 contamination in the food industry.